QUALIFICATION OF THE PRUDENCE PRINCIPLE OF NOTARY ON IMPLEMENT THE POSITION BASED ON ACT OF NOTARY POSITION - Elisabeth Ayustina Putri Korassa Sonbai; Ni Luh Made Mahendrawati; Ida Bagus Agung Putra Santika (Warmadewa Press, 2022)
The purpose of this research is to examine and analyze clearly the scope of the Notary prudence principle on implement his/her position so that definitive or limitative limits are found regarding the Notary prudence principle on implement his/her position. The method used is normative legal research. Data collected through basic regulations, laws and regulations, and legal norm. The theories applied such as the theory of legal protection, the theory of legal certainty, and the theory of responsibility. The results of this research indicate that Article 16 paragraph (1) letters a and m describe the implementation of the Notary position, while the provisions of Article 17 instruct the Notary on implement his/her position to stay away from all prohibitions that are not allowed to be carried out in carrying out his duties, one of which is in the form of doing other job that are contrary to religious norms, decency or propriety that can affect the honor and dignity of the position of a Notary. The provisions of UUJN jo. UUJN-P in particular the provisions of Article 16 paragraph (1) letter a as a violation of the fulfillment of the prudence principle and an administrative violation. Thus, as a Notary, it is advisable to comply more with all the provisions of the UUJN jo. UUJN-P, is careful, thorough and thorough in administering the deed, in order to eliminate the bad intentions of those who deliberately blame and place the Notary as committing an unlawful act, both civil and penal.